(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Cleantech venture capital is that capital that focuses on environmental protection. Green futures are ensured through sustainable Startups that focus on the commercialization of clean tech ventures. This study is based on a holistic overview of the literature relating to cleantech Start-ups. The research article provides five main thematic groups such as policy initiatives for cleantech venture capital, venture capital as an effective source of finance, Impact of venture capital on cleantech Start-ups and challenges and problems faced by Cleantech Start-ups, Clean-tech, and sustainable development. This study broadens the scope of corporate venture capital research. The result shows that the Policy attitude and practices of the Government play an important role in solving barriers to clean Tech and different types of Start-ups are promoted by venture capitalists. It is evidenced that cleantech Start-up may attract venture capital. Some studies argue that due to the high investment risk in cleantech, venture capital captures less attention than conventional technology Startups.